2015
DOI: 10.4236/psych.2015.66064
|View full text |Cite
|
Sign up to set email alerts
|

Parents Who Have Lost a Child to Cancer: What Do They Really Need?

Abstract: In a sample of parents who lost a child to cancer, we investigated their needs before and after their child's death and how these needs were fulfilled. We met parents of AYA (adolescents and young adults) between 15 and 25 years old, who died in Curie Institute between 2000 and 2003. Twentyone families agreed to participate in this study between October 2005 and April 2006. When a family agreed to participate, a semi-structured interview was held in the psycho-oncology unit of the Curie Institute. This intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Research has shown that some parents would like, in addition to follow‐up, bereavement mental health support, sometimes well beyond the first year of bereavement . However, parents, especially minorities, often face barriers in accessing such support . For example, although parents often appreciate services from the institution at which their child was treated, studies have shown that it is emotionally difficult for parents to physically return to the place of treatment, which may be, in part, why home visits are desirable .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that some parents would like, in addition to follow‐up, bereavement mental health support, sometimes well beyond the first year of bereavement . However, parents, especially minorities, often face barriers in accessing such support . For example, although parents often appreciate services from the institution at which their child was treated, studies have shown that it is emotionally difficult for parents to physically return to the place of treatment, which may be, in part, why home visits are desirable .…”
Section: Resultsmentioning
confidence: 99%
“…For example, although parents often appreciate services from the institution at which their child was treated, studies have shown that it is emotionally difficult for parents to physically return to the place of treatment, which may be, in part, why home visits are desirable . Parents are also frequently concerned about the well‐being of their surviving children and want formalized bereaved sibling support . Evidence suggests that there are benefits to grief interventions focusing on the entire family …”
Section: Resultsmentioning
confidence: 99%